2014
DOI: 10.1128/mbio.00945-14
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Growth in Cryptococcus neoformans Is Coordinated with Cell Cycle Progression

Abstract: The fungal pathogen Cryptococcus neoformans has several virulence factors, among which the most important is a polysaccharide capsule. The size of the capsule is variable and can increase significantly during infection. In this work, we investigated the relationship between capsular enlargement and the cell cycle. Capsule growth occurred primarily during the G1 phase. Real-time visualization of capsule growth demonstrated that this process occurred before the appearance of the bud and that capsule growth arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
68
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 74 publications
7
68
0
3
Order By: Relevance
“…When we compare our data including buds to those of García-Rodas et al [6], at first glance they seem to be in agreement: while the mother cell is budding actively, and presumably spending only brief intervals in G1/S, its own capsule does not become thicker. Our data would seem to suggest that this is less because of an intrinsic impairment of capsule growth during G2/M, as suggested by the authors of that study, and more because a mechanism exists whereby capsule polysaccharide might be destined for the capsule of the daughter cell.
10.1080/21505594.2018.1515610-F0004Figure 4.Capsule thicknesses of four mother cells and their buds.
…”
supporting
confidence: 87%
See 2 more Smart Citations
“…When we compare our data including buds to those of García-Rodas et al [6], at first glance they seem to be in agreement: while the mother cell is budding actively, and presumably spending only brief intervals in G1/S, its own capsule does not become thicker. Our data would seem to suggest that this is less because of an intrinsic impairment of capsule growth during G2/M, as suggested by the authors of that study, and more because a mechanism exists whereby capsule polysaccharide might be destined for the capsule of the daughter cell.
10.1080/21505594.2018.1515610-F0004Figure 4.Capsule thicknesses of four mother cells and their buds.
…”
supporting
confidence: 87%
“…The time-lapse images show that the capsule growth is more pronounced in Sab-MOPS, although it was readily observable in both capsule induction conditions (Figure 2(a, b) and Supplemental videos 1–3). We measured the capsule size for several cells and found that the capsule growth follows sigmoidal kinetics with different rates for different cells (Figure 2(c)), as previously observed using measurements based on the Quellung effect [5,6].
10.1080/21505594.2018.1515610-F0002Figure 2.Time-lapse imaging of C. neoformans capsule growth in inducing medium (Sab-MOPS).
…”
supporting
confidence: 67%
See 1 more Smart Citation
“…García-Rodas et al 53 recently demonstrated that benomil, a drug which arrests C. neoformans cell cycle in G2/M, inhibited the capsule growth. We have shown that NaBut arrests cell cycle in G2/M as well (Fig.…”
Section: The Effect Of Hdaci On Melanin Formationmentioning
confidence: 98%
“…We propose that the function of cell-cycle regulators, which are essential for proliferation in the host, merit further investigation as virulence factors. Furthermore, there is evidence that virulence pathways are perturbed when cell-cycle progression is slowed, which suggests direct connections between cell-cycle regulators and virulence pathways [10,11]. …”
Section: Introductionmentioning
confidence: 99%